Pengolahan Data Statistik Asuhan Kesehatan Menggunakan Pivot Tabel Di RSUD Pariaman Periode 01 April – 30 April 2019 - Nada Dwi Altra (Iris Journal of Health Information Management, 2021)
The information contained in the medical record is processed for health care statistics which are used for hospital management decisions. This data processing uses the pivot table feature in Microsoft Excel. Data taken from the Pariaman Hospital for the period 01 April – 30 April 2019, the number of discharged patients was 649 patients with a total of 30 days and 163 beds. Most diagnoses and codes based on ICD-10 were diagnosis of pneumonia with code J18.9 as many as 32 patients. The distribution of patient diagnoses based on defecation was mostly BAB XV (Pregnancy, Childbirth and Puerperium) with 21.27% as many as 140 patients. The most procedures performed were SC (Sectio Caesarea) with a procedure code of 74.99 as many as 8 patients.242.9 (other complications of pregnancy and childbirth) as many as 96 patients. In the RL4a report, the most common age group was the 45-64 year age group with 178 patients with male sex as many as 93 patients, and female as many as 85 patients. Based on the disposition, 607 patients lived and 42 patients died. The distribution of the classification of patient diagnoses based on the Regency/City with the most visits was from Padang Pariaman Regency as many as 393 patients with the highest number from Sungai Limau District as many as 42 patients. After processing the data, BOR is 52%, BTR is 4 times, TI is 4 days, and ALOS is 5 days.